A Comprehensive Macroeconomic Income Determination Model for an Islamic Economy (The Pakistan Development Review, 1994)
Several attempts at modelling the income determination process in an Islamic Economy have been made.l Almost all of these attempts are related to income determination on the demand side of the economy only. To the best of my knowledge no attempt has so far been made to capture the supply-side effects on income determination. Some early Muslim thinkers like Ibn Khaldun (1980) have emphatically stressed the supply-side effects on income determination in a Muslim economy. The main objective of this study is to make an effort to present a comprehensive macroeconomic income determination model for an Islamic economy that takes care of the demand side as far as the goods markets and money markets are concerned and it also covers the supply side of the economy as far as the optimal conditions for hiring of the labour and capital in the factor markets are concerned.